Complex Regulation of gamma-Secretase: from Obligatory to Modulatory Subunits - Gertsik, Natalya; Chiu, Danica; LI, Yueming (Frontiers in Aging Neuroscience, 2015)
gamma-Secretase is a four subunit, 19-pass transmembrane enzyme that cleaves amyloid precursor protein, catalyzing the formation of amyloid beta peptides that form amyloid plaques, which contribute to Alzheimer’s disease pathogenesis. gamma-Secretase also cleaves Notch, among many other type I transmembrane substrates. Despite its seemingly promiscuous enzymatic capacity, gamma-secretase activity is tightly regulated. This regulation is a function of many cellular entities, including but not limited to the essential gamma-secretase subunits, nonessential (modulatory) subunits, and gamma-secretase substrates. Regulation is also accomplished by an array of cellular events, such as presenilin (active subunit of gamma-secretase) endoproteolysis and hypoxia. In this review we discuss how gamma-secretase is regulated with the hope that an advanced understanding of these mechanisms will aid in the development of effective therapeutics for gamma-secretase-associated diseases like Alzheimer’s disease and Notch-addicted cancer